La souffrance faite cause. L’entrée de la traite des êtres humains dans l’arène publique - Milena Jakšić (Genre, Sexualité et Société)
This article explores the potential for mobilization held by the category of the victim in the construction of new causes. Grounded on an analysis of the normative frames through which human trafficking is comprehended, it shows that the establishment of human trafficking as a political cause rested almost entirely on the figure of the victim, constructed in a way which we term « ideal ». The victim, presented as an innocent, naive and vulnerable young woman, provides a focus for indignation, becoming the reason why awareness is raised and action appears urgent. The mobilization potential enclosed in the category of the victim suggests that the fight against human trafficking belongs to the framework of the « politics of pity », which places suffering at the center of the political process. Lastly, the uses of suffering as a rhetorical resource in the construction of new causes explain why commitment against human trafficking has unfurled outside of established forms of protest.